Pyruvic Oxime Nitrification and Copper and Nickel Resistance by a Cupriavidus pauculus, an Active Heterotrophic Nitrifier-Denitrifier - Miguel Ramirez; Jennifer Obrzydowski; Mary Ayers; Sonia Virparia; Meijing Wang; Kurtis Stefan; Richard Linchangco; Domenic Castignetti (The Scientific World Journal)
Heterotrophic nitrifiers synthesize nitrogenous gasses when nitrifying ammonium ion. A Cupriavidus pauculus, previously thought an Alcaligenes sp. and noted as an active heterotrophic nitrifier-denitrifier, was examined for its ability to produce nitrogen gas (N2) and nitrous oxide (N2O) while heterotrophically nitrifying the organic substrate pyruvic oxime [CH3–C(NOH)–COOH]. Neither N2 nor N2O were produced. Nucleotide and phylogenetic analyses indicated that the organism is a member of a genus (Cupriavidus) known for its resistance to metals and its metabolism of xenobiotics. The microbe (a Cupriavidus pauculus designated as C. pauculus strain UM1) was examined for its ability to perform heterotrophic nitrification in the presence of Cu2+ and Ni2+ and to metabolize the xenobiotic phenol. The bacterium heterotrophically nitrified well when either 1 mM Cu2+ or 0.5 mM Ni2+ was present in either enriched or minimal medium. The organism also used phenol as a sole carbon source in either the presence or absence of 1 mM Cu2+ or 0.5 mM Ni2+. The ability of this isolate to perform a number of different metabolisms, its noteworthy resistance to copper and nickel, and its potential use as a bioremediation agent are discussed.